Emotional Artificial Intelligence and Brand Association: A Neuro-Bibliometric Study - Rachman, Adryan; Karina Diandra, Prita; Simon, Febryanti (International Journal Administration, Business & Organization, 2024)
This study conducts a comprehensive bibliometric analysis to explore the research landscape in neuromarketing and brand association. With a growing interest in the neural mechanisms influencing consumer behavior, neuromarketing leverages neuroscientific techniques like fMRI, EEG, and eye tracking to uncover subconscious decision-making processes. The study aims to map research trends, identify key themes, and highlight influential works within this field. Using data from Scopus and Web of Science, the methodology includes examining publication growth, geographic distribution, co-authorship networks, and keyword co-occurrence over the past two decades. The data collection process employed effective keywords such as "neuromarketing," "brand association," "EEG," "fMRI," and "consumer behavior," ensuring a comprehensive dataset of peer-reviewed articles. The findings reveal significant growth in publications, with notable contributions from North America and Europe, and increasing input from Asia. Key insights highlight the central role of emotional engagement, sensory marketing, and the integration of advanced technologies like AI and deep learning in neuromarketing research. The study emphasizes the need for more longitudinal studies to understand the long-term impacts of neuromarketing strategies and calls for cross-cultural comparisons to enhance the global applicability of the findings. Concluding, the research identifies literature gaps and offers practical recommendations for marketers to leverage neuromarketing techniques to boost consumer engagement.